Magnitude distribution and clustering properties of the 3-D seismicity in Central Apennines (Italy). Issue 3 (17th January 2023) - Console, Rodolfo; Vannoli, Paola; Falcone, Giuseppe
SUMMARY: In this paper we deal with statistical features of earthquakes, seeking possible correlations between the Gutenberg–Richter magnitude distribution and the short-term clustering in an area of the Central Apennines, Italy, where significant seismicity with earthquakes exceeding magnitude 6.0 has been repeatedly observed from 1990 to the present. For this purpose, a recently developed version of the ETAS model, incorporating a 3-D spatial triggering kernel, has been adopted. Our analysis has been carried out representing the b -value and the probability of independence of events on six vertical cross-sections suitably related to the seismic structures that are considered responsible of the seismicity observed in the study area. The results of the statistical analysis of the seismicity in the study area have shown a clear distinction between the western normal low-angle fault system, characterized by eastward dip and the eastern normal fault systems, with westward dip. In the former ( Etrurian Fault System ; EFS) we found seismicity with a high b -value and high probability of independence, that is a scarce capacity of producing clusters and strong aftershock sequences. The eastern fault systems of our study area are distinguishable in two main distinct systems, which generated two strong seismic sequences in 1997 and 2016–2017. In the former ( Colfiorito ) sequence the seismicity showed a very low b -value and a modest probability of independence, while in the latter ( Central Italy ) sequence the b -value was significantly higher and the probability of independence had extremely low values (manifesting a high level of clustering). The much higher b -value of the EFS than the other extensional sources could be caused by its peculiar seismotectonic role of discontinuity at the base of the normal active faulting, and its reduced capacity of accumulating stress. This circumstance may be interpreted by a difference in the rheological properties of these fault systems, possibly also in relation to their present status in the earthquake cycle and the presence of strong aftershock sequences.